A Meta-Analysis Study: Barriers to Learning Management Systems in EFL Classrooms - Terzioglu, Yıldız; Kurt, Mustafa (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2019)
The aim of the current meta-analysis is to throw the light on the emerging trends of studies that describe the obstacles in the implementation of Learning Management Systems (LMSs) between 2013 and 2017. A meta-analysis of 107 articles which were listed on Education Resources Information Centre (ERIC) and Web of Science (WOS) was employed in the present study. Data on the distribution of studies on LMS were investigated according to the year of publication, the most frequent challenges facing English as a foreign language teachers (EFL) incorporating LMS, research method, design, sample groups, data collecting tools, countries and the number of authors. The results reveal that the highest number of studies (N=40, 37.38%) occurred in 2017 with an upward trend over the five years. The most common obstacle in the implementation of LMS in classrooms was discovered as the lack of teacher training (N=32, 29.91%). Moreover, the most frequently applied research method was the quantitative technique (N=51, 47.66%). The descriptive model (N=32, 29.91%) was found as the most frequent research model. In addition, the most common sample group included undergraduate and graduate students (N=46, 42.99%). The most prominent data collection tool pointed to questionnaires (N=47, 43.93%). According to the results, the most frequent studies took place in China (N=14, 13.08%). There is a growing trend in studies with only one author (N=52, 48.6%). The conclusion states the implications of the current research and recommendations for further research.